Photodynamically activated chlorogenic acid-based antimicrobial packaging films for cherry preservation - Han, Ximei; Chen, Jiayi; Wang, Qian; Zhang, Jie; Mi, Jiaqi; Feng, Jianxing; Du, Ting; Wang, Jianlong; Zhang, Wentao (Food chemistry, 2025)
Natural photosensitizers offer promising and sustainable solutions to the challenges of food preservation. This study investigates the potential of chlorogenic acid (CA), a naturally occurring phenolic compound with dual photoactive and antimicrobial properties. Under Xenon lamp irradiation (100 mW/cm2), CA at a concentration of 0.5 mg/mL demonstrated significant antimicrobial efficacy against both Staphylococcus aureus (106 CFU/mL) and Escherichia coli (105 CFU/mL). To enhance the practical applicability of CA for cherry preservation, CA was incorporated into agar (AG) films, which exhibited superior physicochemical and mechanical properties, including increased tensile strength and improved gas permeability. Implementation of CA-AG films prolonged the storage duration of cherries by 9 days through effective quality retention and suppression of microbial contamination. This research highlights the potential of CA as an environmentally friendly and functional solution for advanced food preservation technologies. •The photodynamic antibacterial activity of chlorogenic acid was discovered.•CA incorporated into agar matrix for preparing composite films.•Combination of PDI antibacterial activity and CA-AG composite films.•CA-AG composite films extended shelf-life and protected quality of cherries.